Understanding the Link between High-Speed Rail and Economic Growth - Yangailo, Tryson (International Research Journal of Business Studies, 2024)
This study systematically reviews the literature on high-speed rail (HSR) and its impact on economic growth, revealing significant development potential, but with regional disparities. Larger cities often benefit more than smaller ones, highlighting the need for strategic policies to ensure inclusive growth. Initiatives such as supporting local innovation, retaining talent, and addressing accessibility gaps are essential. Current research uses quantitative methods and focuses on specific countries, suggesting broader qualitative approaches are needed. Effective implementation of HSR requires more than infrastructure; success depends on factors such as high population density, supportive land use regulations, and investment in education. Caution is advised for developing countries that lack national HSR policies or technological innovation. Tailored regulations and localized support are critical to optimize economic benefits and address uneven growth, as the viability of HSR depends on favorable geographical and economic conditions.